Claudin-10a Deficiency Shifts Proximal Tubular Cl- Permeability to Cation Selectivity via Claudin-2 Redistribution. Issue 4 (April 2022) - Breiderhoff, Tilman; Himmerkus, Nina; Meoli, Luca; Fromm, Anja; Sewerin, Sebastian; Kriuchkova, Natalia; Nagel, Oliver; Ladilov, Yury; Krug, Susanne M.; Quintanova, Catarina; Stumpp, Meike; Garbe-Schönberg, Dieter; et al.
Significance Statement: Claudin-10 is a tight junction protein expressed along the nephron. The claudin-10a isoform is a paracellular anion channel; claudin-10b facilitates paracellular Na + transport in the thick ascending limb. Mutations in the CLDN10 gene that affect either claudin-10b or both isoforms cause HELIX syndrome. This study demonstrates that claudin-10a is essential for paracellular Cl - transport in the proximal tubule. In mice lacking claudin-10a, additional cation-selective claudin-2 incorporates into proximal tubule tight junctions. This turns paracellular anion into cation preference, with renal retention of calcium and magnesium and hypermagnesemia. Loss of anion permeability triggers compensation measures within the proximal tubule and in more distal parts of the nephron. Data from the claudin-10a–deficient mouse suggest mutations affecting both isoforms may result in a more severe electrolyte imbalance in HELIX syndrome. Visual Abstract: Abstract : Background: The tight junction proteins claudin-2 and claudin-10a form paracellular cation and anion channels, respectively, and are expressed in the proximal tubule. However, the physiologic role of claudin-10a in the kidney has been unclear. Methods: To investigate the physiologic role of claudin-10a, we generated claudin-10a–deficient mice, confirmed successful knockout by Southern blot, Western blot, and immunofluorescence staining, and analyzed urine and serum of knockout and wild-type animals. We also used electrophysiologic studies to investigate the functionality of isolated proximal tubules, and studied compensatory regulation by pharmacologic intervention, RNA sequencing analysis, Western blot, immunofluorescence staining, and respirometry. Results: Mice deficient in claudin-10a were fertile and without overt phenotypes. On knockout, claudin-10a was replaced by claudin-2 in all proximal tubule segments. Electrophysiology showed conversion from paracellular anion preference to cation preference and a loss of paracellular Cl - over HCO3 - preference. As a result, there was tubular retention of calcium and magnesium, higher urine pH, and mild hypermagnesemia. A comparison with other urine and serum parameters under control conditions and sequential pharmacologic transport inhibition, and unchanged fractional lithium excretion, suggested compensative measures in proximal and distal tubular segments. Changes in proximal tubular oxygen handling and differential expression of genes regulating fatty acid metabolism indicated proximal tubular adaptation. Western blot and immunofluorescence revealed alterations in distal tubular transport. Conclusions: Claudin-10a is the major paracellular anion channel in the proximal tubule and its deletion causes calcium and magnesium hyper-reabsorption by claudin-2 redistribution. Transcellular transport in proximal and distal segments and proximal tubular metabolic adaptation compensate for loss of paracellular anion permeability.